PROFIL KOMPETENSI GURU MATEMATIKA DITINJAU MELALUI TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) DILIHAT DARI SERTIFIKASI GURU - Jihan Zulfia Firda; Maryono Maryono; Muniri Muniri (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
This research describes competency profile of certified mathematics teacher(s) and non-sertified mathematics teacher(s) which were investigated through TPACK. Applying a qualitative approach to case study research. The data were obtained through questionnaires, interviews, and observation techniques. Determining subjects was carried out using a purposive sampling technique, 2 types of subjects were obtained: 2 certified mathematics teachers and 2 non-certified mathematics teachers. Data analysis applying the spiral model by Creswell. Checking the validity of the data was carried out using observation and data triangulation techniques. The results of this research show: (1) certified mathematics teachers have very good TPACK abilities, they are able to choose, use and teach by ascertaining whether the learning class conditions support applying technology or not, (2) meanwhile, the results on non-certified mathematics teachers show good TPACK abilities. This means that teachers can choose, use, and teach learning that combines technology, content, and teaching approaches, but however they experience difficulties in adjusting learning using technology at the first time they used it.